Event Studies of High‐Latitude FACs With Inverse and Assimilative Analysis of AMPERE Magnetometer Data. Issue 3 (5th March 2020) - Shi, Yining; Knipp, Delores J.; Matsuo, Tomoko; Kilcommons, Liam; Anderson, Brian
Abstract: We present examples of high‐latitude field‐aligned current (FAC) and toroidal magnetic potential patterns in both hemispheres reconstructed at a 2‐min cadence using an updated optimal interpolation (OI) method that ingests magnetic perturbation data provided by the Active Magnetosphere and Planetary Electrodynamics Response Experiment (AMPERE) program. A solstice and an equinoctial event are studied to demonstrate the reconstructed patterns and to provide scientific insights into FAC response to different solar wind drivers. For the 14 June 2011 high‐speed stream event with mostly northward B z driving, we found persistently stronger FACs in the Northern Hemisphere. Extreme interhemispheric asymmetry is associated with the interplanetary magnetic field (IMF) direction and large dipole tilt, consistent with earlier studies. FAC asymmetries seen during an isolated substorm can be attributed to dipole tilt. During relatively low geomagnetic activity, the FAC response to IMF B x changes is identified. For the 17–18 March 2013 period, we provide global snapshots of rapid FAC changes related to an interplanetary shock passage. We further present comparisons between instantaneous and mean behaviors of FAC for the solar wind sheath passage and interplanetary coronal mass ejection southward B z interval and northward B z intervals. We show that (1) sheath passage results in strong FAC and high variation in the dayside polar cap region and pre‐midnight region, different from the typical R1/R2 currents during prolonged southward B z ; (2) four‐cell reverse patterns appear during northward B z but are not stable; and (3) persistent dawn‐dusk asymmetry is seen throughout the storm, especially during an extreme substorm, likely associated with a dawnside current wedge. Key Points: Magnetic potential and FAC patterns are reconstructed with 2‐min cadence using optimal interpolation method with new background error covariance We illustrate asymmetries in FACs due to seasonal and IMF B y and B x effects We reconstruct at high cadence the FAC response to passage of an IP shock and development of an extreme substorm